Creating an Agile enterprise - Humble, Jez; Molesky, Joanne; O'Reilly, Barry ([O'Reilly Media], 2018)
Implementing an enterprise-level continuous improvement process is a prerequisite for any ongoing large-scale transformation effort (such as adopting an agile approach to software delivery) at scale. True continuous improvement never ends because, as our organization and environment evolve, we find that what works for us today will not be effective when conditions change. High-performance organizations are constantly evolving to adapt to their environment.
Publication information from resource description page (Safari, viewed March 14, 2018). - Online resource; title from title page (viewed March 14, 2018)
Keywords: Project management; Agile software development; Business planning; Production control; Industrial management -- Quality control; Gestion de projet; Méthodes agiles (Développement de logiciels); Production; Contrôle; Gestion d'entreprise; Qualité; Contrôle; Industrial management; Quality control